2012
DOI: 10.1016/j.amjcard.2011.08.043
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Adverse Outcome in Adolescents and Adults With Isolated Left Ventricular Noncompaction

Abstract: Isolated left ventricular noncompaction is a rare form of primary cardiomyopathy. Although increasingly diagnosed, data on the outcomes are limited. To define the predictors of adverse outcomes, we performed a retrospective analysis of a prospectively defined cohort of consecutive patients (age >14 years) diagnosed with left ventricular noncompaction at a single center. The baseline characteristics included presentation with a cardiovascular complication (i.e., decompensated heart failure, systemic embolic eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
58
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 20 publications
10
58
0
4
Order By: Relevance
“…16 As in all series of patients with LVNC the absence of generally accepted diagnostic criteria for this disease entity remains a dilemma. While the criteria proposed by our group may be too sensitive, particularly in black individuals, they may identify symptomatic patients of a Caucasian population at high risk for cardiovascular complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 As in all series of patients with LVNC the absence of generally accepted diagnostic criteria for this disease entity remains a dilemma. While the criteria proposed by our group may be too sensitive, particularly in black individuals, they may identify symptomatic patients of a Caucasian population at high risk for cardiovascular complications.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 These criteria have been shown to identify a subset of symptomatic patients at risk for adverse outcome. 15 In brief, the criteria include a combination of 1) segmental thickening of the left ventricular myocardial wall 2) consisting of an inner non-compacted and an outer compacted layer with 3) a thickness ratio ≥ 2:1 at end-systole, measured in the were assessed according to established guidelines for two-dimensional echocardiography.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the presence of heart failure, history of sustained ventricular tachycardia or systemic thromboembolism seem to be associated with an unfavourable prognosis among other phenotypes with distinct outcomes [21,22]. In a recent study, mortality did not differ significantly between patients with isolated LVNC and control patients with dilated cardiomyopathy, [24] suggesting that LV dysfunction rather than the phenotype itself is the risk-increasing mechanism.…”
Section: Clinical Manifestationsmentioning
confidence: 98%
“…Studies of older children and adults have reported a high incidence of severe manifestations [7,17,[19][20][21][22] such as LV dysfunction, thromboembolic events, which probably originate in the deep intertrabecular recesses, arrhythmias, and sudden death. Other studies, however, have found a much lower incidence of complications, suggesting subclinical or milder cases [23].…”
Section: Clinical Manifestationsmentioning
confidence: 99%